Five-step preparation of the pilot of civil aviation in a system of continuous training - Коростелев, A. E. (Proceedings of National Aviation University (archive), 2000)
Considered is the correlation between educational levels: gualified worker (operator ), junior specialist, bachelor, specialist and master. A minimal number of hours of practical training is defined for each stage (flight hours on airplane) and aircraft simulator necessary for issuing a respective certificate (PPL or CPL) with necessary respective qualification marks being inserted